2021
DOI: 10.1111/tmi.13544
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of glucose metabolism and blood pressure among Ethiopian individuals with HIV/AIDS after one‐year of antiretroviral therapy

Abstract: Objective Better understanding of glucose metabolism in patients with HIV after initiating antiretroviral therapy (ART) is important to target treatment and follow‐up for diabetes risk and other non‐communicable diseases in resource‐limited settings. The aim of this study was to assess the changes and predictors of glucose metabolism and blood pressure among patients with HIV on ART for 12 months. Methods One‐year follow‐up of Ethiopian patients with HIV after initiation of ART was done. Outcomes were changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 40 publications
(42 reference statements)
0
6
0
1
Order By: Relevance
“…Few of the patients observed a strong non-linear increase in FPG, with a rising growth rate in the last few years of follow-up after a slight decrease in the first year. A recent study also showed that FPG declined and insulin increased during 12 months of ART, indicating that there might be an improvement in insulin secretion and health ( 30 ). In addition, some studies have shown that the longer the duration of HAART, the higher the risk of diabetes ( 31 , 32 ), reflecting the possible cumulative effects of HIV infection or ART on diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Few of the patients observed a strong non-linear increase in FPG, with a rising growth rate in the last few years of follow-up after a slight decrease in the first year. A recent study also showed that FPG declined and insulin increased during 12 months of ART, indicating that there might be an improvement in insulin secretion and health ( 30 ). In addition, some studies have shown that the longer the duration of HAART, the higher the risk of diabetes ( 31 , 32 ), reflecting the possible cumulative effects of HIV infection or ART on diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…For these studies, follow-up time ranged from 1 month to 1 year. The majority of the articles reported an increase in systolic BP (4.0-7.0 mmHg) [21,23,24] and half of them found an increase in diastolic BP (2.3-6.6 mmHg) [23,24] in the year following ART initiation. Two studies measure at 6-month follow-up and report inconsistent results [22,23].…”
Section: Blood Pressure Trajectories In Short Follow-up Studies (<2 Y...mentioning
confidence: 99%
“…Sample size and demographic characteristics were heterogenous across short follow-up studies. Three studies had predominantly male cohorts [22][23][24], while one had a predominantly female cohort [21]. Race and ethnicity were also heterogeneous among those cohorts.…”
Section: Blood Pressure Trajectories In Short Follow-up Studies (<2 Y...mentioning
confidence: 99%
See 1 more Smart Citation
“…Outros estudos corroboram com o aumento da PA ao longo do tratamento. Uma pesquisa realizada Etiópia com 318 PVHIV, foi evidenciado que desde os 12 meses após o início da TARV, há elevação da PA (AMARE et al, 2021). Resultado preocupante, considerando a associação de maiores níveis pressóricos ao aumento do risco de mortalidade em PVHIV, sobretudo os que já iniciam o tratamento com histórico de HA (BATAVIA et al, 2018).…”
Section: Conforme Recomendação Da Diretriz Brasileira De Dislipidemia...unclassified